2002
DOI: 10.1016/s1472-6483(10)61915-3
|View full text |Cite
|
Sign up to set email alerts
|

A novel approach for patients at risk for ovarian hyperstimulation syndrome: elective transfer of a single zona-free blastocyst on day 5

Abstract: In this preliminary prospective randomized study of 420 patients undergoing ovarian stimulation for IVF/intracytoplasmic sperm injection (ICSI), 17 patients (4%) developed moderate to severe ovarian hyperstimulation syndrome (OHSS). Re-evaluation for OHSS on day 4 and 6 after oocyte retrieval identified one patient with continuous risk for severe OHSS, resulting in cancellation of the transfer (1/17, 5.8%). Prospectively, two of three patients had the zona pellucida of the blastocyst removed by pronase exposur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
9
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Related studies have also indicated that recruitment at the blastocyst stage yields better results than selection at day 3, which merely depends on the morphologic evaluation of embryos. These studies also claim that pregnancy rates of up to 50% can be acquired by the transfer of blastocysts when compared with embryo transfer at the cleavage stage ( 15 , 16 , 17 , 18 , 19 , 20 , 21 ) . Similarly, it has been shown that the risk of aneuploidy was significantly lower in day 5 embryos than in day 3 embryos ( 22 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Related studies have also indicated that recruitment at the blastocyst stage yields better results than selection at day 3, which merely depends on the morphologic evaluation of embryos. These studies also claim that pregnancy rates of up to 50% can be acquired by the transfer of blastocysts when compared with embryo transfer at the cleavage stage ( 15 , 16 , 17 , 18 , 19 , 20 , 21 ) . Similarly, it has been shown that the risk of aneuploidy was significantly lower in day 5 embryos than in day 3 embryos ( 22 ) .…”
Section: Discussionmentioning
confidence: 99%
“…Frozen-thawed embryo transfer appears to not only reduce the risk of multiple gestation but also avoid the ovarian hyperstimulation syndrome [1,2]. Blastocyst culture techniques have improved and the blastocysts can be cyropreserved by vitrification [3].…”
Section: Introductionmentioning
confidence: 99%
“…Severe ascites, hypovolemia, or electrolyte imbalance did not occur, and no patients were hospitalized. employ single blastocyst transfer in patients at risk of developing severe OHSS (108,109). Such a strategy results in a negligible multiple gestation rate, which purportedly is associated with more severe OHSS presumably secondary to higher hCG levels.…”
Section: Gnrh-antagonists and Ohssmentioning
confidence: 99%